Strategi Pengembangan Pantai Pengklik Sebagai Tujuan Wisata Alternatif Di Kabupaten Bantul - I Putu Hardani HD (Universitas Bina Sarana Informatika, 2019)
Abstract - Bantul Regency is one of 5 (five) districts in Yogyakarta. Tourism located in Bantul is currently growing rapidly, one of the tourist destinations are much in demand by tourists when traveling to Bantul is a beach tour. However, many tourists who visit the beaches are famous only while a lot of beach tourism that has not been famous that basically has the same charm with the beaches. One of them is Pengklik Beach located in Bantul Regency. Therefore the researchers are interested to conduct research with the title